1996
DOI: 10.1016/s0022-5347(01)65790-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pediatric Urolithiasis Between 1984 and 1994

Abstract: 2016-12-26T15:09:09

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 19 publications
2
23
0
2
Order By: Relevance
“…In 14% of the pediatric urolithiasis cases in Europe, no cause was identified, while in the USA this rate was reported to be 18.7-28.3% [15,31,39]. In our country a study held in 1997 reported the rate of idiopathic urolithiasis as 12%.…”
Section: Discussionmentioning
confidence: 75%
“…In 14% of the pediatric urolithiasis cases in Europe, no cause was identified, while in the USA this rate was reported to be 18.7-28.3% [15,31,39]. In our country a study held in 1997 reported the rate of idiopathic urolithiasis as 12%.…”
Section: Discussionmentioning
confidence: 75%
“…Other abnormalities were hyperoxaluria (26.5%), hyperuricosuria (25.4%) hyperphosphaturia (20.8%) and cystinuria (5.7%). Among the published studies, a metabolic cause of pediatric urolithiasis is described in -95% of cases, depending on the study [20,[26][27][28][29]. In a multicenter study, Stapleton et al [30] reported a significant association of idiopathic hypercalciuria with a high risk of future urolithiasis in children with hematuria.…”
Section: Discussionmentioning
confidence: 99%
“…In children under 1 year of age, restlessness is a common presenting symptom [10]. If the stone is in the lower urinary tract, other urinary symptoms may be present such as lower quadrant pain, groin/scrotal pain, dysuria, or difficulty voiding [11,12].…”
Section: Clinical Presentation Of Pediatric Urolithiasismentioning
confidence: 99%
“…Urinary tract abnormalities predisposing to stasis are a risk factor for urolithiasis [11]. Urinary obstruction due to ureteropelvic junction obstruction may result in stasis and predispose to stone formation.…”
Section: Medical Historymentioning
confidence: 99%